The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1464-410x.2006.06416.x
|View full text |Cite
|
Sign up to set email alerts
|

The rising prevalence of androgen deprivation among older American men since the advent of prostate‐specific antigen testing: a population‐based cohort study

Abstract: OBJECTIVE To investigate the effect of efforts in the early detection of prostate cancer using prostate‐specific antigen (PSA) testing in the USA, by estimating the regional prevalence of androgen deprivation therapy (ADT) among older men in 1993–2000, and correlating the prevalence with early detection and aggressive treatment rates in 1987–91, as some authors predicted that ADT, a treatment traditionally reserved for advanced prostate cancer, would become less common over time as a result of such efforts. PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 35 publications
2
58
1
Order By: Relevance
“…Although other studies showed marked increases in the use of ADT for men with nonmetastatic disease since the early 1990s [8][9][10], for both white and black men [22], there were no similar increases in the use of ADT for metastatic disease during this time.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although other studies showed marked increases in the use of ADT for men with nonmetastatic disease since the early 1990s [8][9][10], for both white and black men [22], there were no similar increases in the use of ADT for metastatic disease during this time.…”
Section: Discussionmentioning
confidence: 83%
“…The use of ADT has increased greatly since the early 1990s among American men with nonmetastatic prostate cancer [8][9][10], but few data are available about patterns of ADT in men with metastatic prostate cancer. A recent study of men who died from prostate cancer during 1991-2000 found that about a quarter of men did not receive ADT before death, and black men were much less likely than white men to receive ADT [11].…”
Section: Introductionmentioning
confidence: 99%
“…4 Since Huggins et al 5 demonstrated the androgen dependence of prostate cancer, androgen deprivation therapy (ADT) has been increasingly applied in the treatment for prostate cancer. ADT with gonadotropin-releasing hormone agonist or bilateral orchiectomy is the mainstay of treatment for metastatic and recurrent prostate cancer 6 and may be beneficial to men with locally advanced disease. [7][8][9] Although ADT offers important clinical benefits, it is associated with a variety of complications such as hot flushes, anaemia, sexual dysfunction, changing body composition, osteoporosis and fractures, and increased risk for diabetes and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an impressive improvement in survival rate, and this success led to numerous studies exploring this concept. In addition, with the longer duration of LHRH dosage intervals and the reduced negative impact to patients' selfimage and cosmetic appearance [7,8] , LHRH agonist therapy became more popular than surgical castra tion [22,23] . Because medical castration is reversible and has less of a psychiatric impact than surgical castration, several new trials have been conducted in different clinical situations.…”
Section: Wwwchinapharcom Lin Yh Et Almentioning
confidence: 99%